Small private irrigation: a thriving but overlooked sector - Fraiture, Charlotte de; Giordano, Meredith A. (Elsevier, 2014)
An increasing number of smallholder farmers engage in irrigation using their own resources. They buy or rent irrigation equipment and draw water from nearby sources without depending on or without interference from public agencies or water user associations. The individualization of Agricultural Water Management has been ongoing for several decades in South Asia where most irrigation now takes place from privately owned wells. Recently, small private irrigation is emerging also in sub Saharan Africa. It is farmer-driven, responds to a genuine demand from smallholders and has substantial potential for poverty alleviation and rural development. In many countries the area under privately managed and owned irrigation is larger than under public irrigation schemes. However, the individualization of irrigation and its spontaneous, unchecked spread pose challenges to equitable access to and sustainable management of water resources. Irrigation investments and research efforts have largely focused on the underperforming public irrigation sector, ignoring small private irrigation. This special issue describes and analyzes this thriving but overlooked sector, drawing from examples from five countries in Sub-Saharan Africa and two states in India. The authors explore ways to enhance the potential of small private irrigation for all, without jeopardizing the sustainability of the available water resources.